Abundance and sinking of particulate black carbon in the western Arctic and Subarctic Oceans - Fang, Ziming (Sci Rep, 2016)
The abundance and sinking of particulate black carbon (PBC) were examined for the first time in the western Arctic and Subarctic Oceans. In the central Arctic Ocean, high PBC concentrations with a mean of 0.021 ± 0.016 μmol L(−1) were observed in the marginal ice zone (MIZ). A number of parameters, including temperature, salinity and (234)Th/(238)U ratios, indicated that both the rapid release of atmospherically deposited PBC on sea ice and a slow sinking rate were responsible for the comparable PBC concentrations between the MIZ and mid-latitudinal Pacific Ocean (ML). On the Chukchi and Bering Shelves (CBS), PBC concentrations were also comparable to those obtained in the ML. Further, significant deficits of (234)Th revealed the rapid sinking of PBC on the CBS. These results implied additional source terms for PBC in addition to atmospheric deposition and fluvial discharge on the western Arctic shelves. Based on (234)Th/(238)U disequilibria, the net sinking rate of PBC out of the surface water was −0.8 ± 2.5 μmol m(−3) d(−1) (mean ± s.d.) in the MIZ. In contrast, on the shelves, the average sinking rate of PBC was 6.1 ± 4.6 μmol m(−3) d(−1). Thus, the western Arctic Shelf was probably an effective location for burying PBC.